Croatian Traditional Apple Varieties: Why Are They More Resistant to Plant Diseases? - Ante Lončarić; Tihomir Kovač; Ana-Marija Gotal; Maria Celeiro; Marta Lores (Biology and Life Sciences Forum, 2021)
This study aimed to detect, quantify and compare the amounts of chlorogenic acid, phloridzin and quercetin in Croatian traditional and conventional apple varieties by HPLC-PDA. The results showed that Croatian traditional apple varieties had significantly higher amounts of chlorogenic acid (30.29 ± 0.34 mg/100 g dw), phloridzin (3.12 ± 0.01 mg/100 g dw) and quercetin (11.68 ± 0.09 mg/100 g dw) detected for varieties Božičnica, Mašanka and Petrovnjača, respectively. The highest contents of the total phenolic acids, dihydrochalcones and flavonols were detected in Božićnica (31.94 ± 0.65 mg/100 g dw), Mašanka (3.52 ± 0.52 mg/100 g dw) and Fuji (19.11 ± 0.56 mg/100 g dw). These results present the beginning of the research on the resistance of Croatian traditional apple varieties to plant diseases.